PERLINDUNGAN HUKUM TERHADAP PELAKU PEDAGANG PERANTARA DAN PERANTARA PERDAGANGAN MENURUT UNDANG-UNDANG No. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Faridy; Yakin, Ainul (Fakultas Hukum Universitas Islam Indragiri, 2023)
This article discusses legal protection for intermediary traders and Trade Intermediaries. To discuss legal issues studied using a normative legal research paradigm. The approaches used in this research are the statute approach and the conceptual approach. The legal materials used in this research are primary legal materials which include related laws and regulations and secondary legal materials sourced from books and scientific legal journals. The results of this research are that intermediary traders and trade intermediaries are processes of ordering, granting power of attorney, or agency. The main basis of brokerage activities is a contract or agreement. Legal protection is in the form of an agreement which contains a series or sentences containing promises or undertakings spoken or made in writing by the parties making the agreement. These intermediary traders must of course be given adequate legal protection, while the UUPK does not specifically mention that intermediaries may be involved between business actors and final consumers.